2020
DOI: 10.1111/and.13561
|View full text |Cite
|
Sign up to set email alerts
|

Costus afer leaf extract protects against testicle damage caused by cyclosporine A in adult male Wistar rats through an antioxidant mechanism

Abstract: Cyclosporine A is one of the most widely used drugs in organ transplant and oncology patients. But its use is accompanied by many toxicities. This study aimed to investigate the possible protective effect of Costus afer (C. afer) leaf extract on cyclosporine A‐induced testicular toxicity. This study was carried out on 40 adult male Wistar rats were divided into four groups: control, C. afer, cyclosporine A and cyclosporine A+ C. afer groups. The investigations include genital weight, sperm count and characters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…The production of fewer spermatozoa could be caused by changes in the marker testicular enzymes activities linked with changes in histopathology. Previous reports (Khattab and Mansoury, 2020;Shukry et al, 2020) have shown that cyclosporine causes histological changes in the testes, including germinal cell atrophy, necrosis, and degeneration, interstitial edema, vascular congestion, and spillage of immature spermatogonia and spermatocytes into the lumen of seminiferous tubules. The group cotreated with lutein showed improved testicular histopathological features which agree with the findings of Fatani et al (2015) and , demonstrating that lutein treatment restores testicular function and normal spermatogenesis.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The production of fewer spermatozoa could be caused by changes in the marker testicular enzymes activities linked with changes in histopathology. Previous reports (Khattab and Mansoury, 2020;Shukry et al, 2020) have shown that cyclosporine causes histological changes in the testes, including germinal cell atrophy, necrosis, and degeneration, interstitial edema, vascular congestion, and spillage of immature spermatogonia and spermatocytes into the lumen of seminiferous tubules. The group cotreated with lutein showed improved testicular histopathological features which agree with the findings of Fatani et al (2015) and , demonstrating that lutein treatment restores testicular function and normal spermatogenesis.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, there is evidence that long-term use of cyclosporine induces testicular damage leading to reduced sperm count and motility through a variety of mechanisms that involve oxidative stress (Lee, 2013;Pan et al, 2018). Epidemiological and experimental investigations have shown that cyclosporine reduces testosterone synthesis, causes DNA damage, and raises the apoptotic index of germinal cells in seminiferous tubules (Turk et al, 2007(Turk et al, , 2010Pan et al, 2018;Ghazipoor et al, 2020;Khattab et al, 2020). It has recently been demonstrated that phytochemicals derived from herbs and spices like chamomile (Al-Dabbagh et al, 2019), curcumin (Huang et al, 2018), lycopene (Ateşşahin et al, 2007), Nacetylcysteine (Duru et al, 2008), black grape extract (Ergüderİ et al, 2005), morin (Ben-Azu et al, 2018, lutein (Buscemi et al, 2018) and taurine (Hagar et al, 2004;Oyovwi et al, 2021) possess powerful antioxidant and neuroprotective activities.…”
Section: Introductionmentioning
confidence: 99%
“…This will lead to a decrease in LH‐mediated testosterone synthesis and secretion from the Leydig cell. Cyclosporine also affected the serum level of follicle‐stimulating hormone by decreasing the phagocytic mechanism of Sertoli cells (Khattab & Mansoury, 2020). The decrease in the luteinizing hormone could also be a result of a decreased expression of the Leydig cell.…”
Section: Discussionmentioning
confidence: 99%
“…The use of different immunosuppressant for the treatment of autoimmune diseases and transplantation has been linked with the endocrine disruption, damage on the reproductive tissues, and alteration in the hormone activity. A good example is cyclosporine A. Cyclosporine is an immunophilin modulator and a calcineurin inhibitor which have serious side effects on multiple organs including the reproductive system (Khattab & Mansoury, 2020). Studies have linked the use of cyclosporine with infertility via oxidative stress mechanism (Drobnis & Nangia, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation